1976
DOI: 10.1080/00071667608416279
|View full text |Cite
|
Sign up to set email alerts
|

Chick embryo heart rate during the last week of incubation: Population studies

Abstract: 1. A technique has been developed for the study of embryonic heart rate during the last week of incubation in a population of 84 embryos. 2. Heart rate is characteristic for a particular embryo but there are clear differences between individuals. 3. The population mean heart rate decreased from 262 beats/min at 14 d to a minimum of 250 beats/min at 19-5 d and then increased rapidly to more than 270 beats/min before hatching. 4. This pattern was repeatable and independent of the flock age. 5. Embryonic heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…During the same incubation period Antoni and Diliger (1981) obtained similar results, while Laughlin et al (1975) and Cain et al (1967) recorded the number of heartbeats to decrease. As embryonic development went on (a�er 16 days of incubation), similarly like Laughlin et al (1975) and Cain et al (1967) we observed the frequency of heart work to drop from 215 to 205 contractions per minute, while the lowest values (161 per minute) were recorded on the last day of incubation when all eggs were pipped (Table 1).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…During the same incubation period Antoni and Diliger (1981) obtained similar results, while Laughlin et al (1975) and Cain et al (1967) recorded the number of heartbeats to decrease. As embryonic development went on (a�er 16 days of incubation), similarly like Laughlin et al (1975) and Cain et al (1967) we observed the frequency of heart work to drop from 215 to 205 contractions per minute, while the lowest values (161 per minute) were recorded on the last day of incubation when all eggs were pipped (Table 1).…”
Section: Resultssupporting
confidence: 65%
“…Laughlin et al (1975) reported that during pipping, the heart rate increases to 270 contractions per minute.…”
Section: Resultsmentioning
confidence: 99%
“…We were interested in measuring the embryonic HR during normal incubation of the largest living bird in terms of its developmental pattern and allometric relationship with egg mass. The developmental patterns of prenatal HR of domesticated precocial birds show a trend to decrease towards pipping time (Laughlin et al, 1976;Tazawa et al, 1991). Thus it was predicted that the daily HR of ostrich embryos would also decrease during the last stages of incubation and mean HR would be around 160 beats/min.…”
Section: Introductionmentioning
confidence: 98%
“…In domestic chicks and Japanese quail, heart rate increases during the 24 hr prior to hatching and may be an influential factor in the hatching process (Laughlin, Lundy, & Tait, 1976;Ockleford & Vince, 1977). Previous research indicates that exposing turkeys and leopard geckos to light accelerates hatching time (Fairchild & Christensen, 2000;Sleigh & Birchard, 2001).…”
Section: Discussionmentioning
confidence: 97%